Differences in risk for type 1 and type 2 ovarian cancer in a large cancer screening trial - Terada, Keith Y. (J Gynecol Oncol, 2016)
OBJECTIVE: To investigate the role of previous gynecologic surgery, hormone use, and use of non-steroidal anti-inflammatory drugs on the risk of type 1 and type 2 ovarian cancer. METHODS: We utilized data collected for the Prostate, Lung, Colorectal, and Ovarian cancer screening trial. All diagnosed ovarian cancers were divided into three groups: type 1, endometrioid, clear cell, mucinous, low grade serous, and low grade adenocarcinoma/not otherwise specified (NOS); type 2, high grade serous, undifferentiated, carcinosarcoma, and high grade adenocarcinoma/NOS; and other: adenocarcinoma with grade or histology not specified, borderline tumors, granulosa cell tumors. The odds ratios for type 1, type 2, and other ovarian cancers were assessed with regard to historical information for specific risk factors. RESULTS: Ibuprofen use was associated with a decrease in risk for type 1 ovarian cancer. Tubal ligation and oral contraceptive use were associated with a decrease in risk for type 2 ovarian cancer. A history of ectopic pregnancy was associated with a decreased risk for all ovarian cancers by almost 70%. CONCLUSION: These findings support the hypothesis that carcinogenic pathways for type 1 and type 2 ovarian cancer are different and distinct. The marked reduction in all ovarian cancer risk noted with a history of ectopic pregnancy and salpingectomy implies that the fallopian tube plays a key role in carcinogenesis for both type 1 and type 2 ovarian cancer.